Diagnóstico del riesgo laboral para el talento humano del Hospital “Dr. Aníbal González Álava” del cantón Bolívar provincia de Manabí - Pincay Santana, Jacinta Verónica (2013)
This thesis has allowed a diagnostic of occupational hazard which is exposed health staff that handles waste in the Hospital “Dr. Aníbal González Alava” and establish an improvement plan to help reduce the risk labor officers. For the execution of this work was used as tools FODA matrix, matrix involved, the observation in each of the areas surveyed, the highest authority to interview an the survey was directed to all personnel involved in waste management, an these a total of 68 respondents, resulting in the occupational risk factors were present: Physical: noise, temperature extremes, chemicals, desinfectants, solvents, sacasarros, powders; biological: tetanus, hepatitis, HIV; ergonomics; cargo handling, repetitive movements, awkward postures that are linked with many elements that relate to the activity performed by the employees, diagnosing the existence of occupational hazard with a low level but on the grounds that buy not complying with the rules waste management an biosafety measures, this can be increased in virtue, a structured plan for improvement based on those already mentioned, which were considered in accordance with the rules of the institution achieving the implementation of activities or solutions with their respective officers and probable date of the execution of the plan, having clear that to eliminate difficulties requires a continuous monitoring allows solving problems that arise.